2016
DOI: 10.1080/10810730.2016.1222030
|View full text |Cite
|
Sign up to set email alerts
|

Tapping Into Motivations for Drinking Among Youth: Normative Beliefs About Alcohol Use Among Underage Drinkers in the United States

Abstract: Social norms affect human behavior, and underage drinking is no exception. Using the theory of normative social behavior (TNSB), this paper tested the proposition that the association between perceptions about the prevalence of drinking (descriptive norms) and underage drinking is strengthened when perceived pressures to conform (injunctive norms) and beliefs about the benefits of drinking (outcome expectations) are high. This proposition was tested on a nationally representative sample of underage drinkers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
2
14
0
5
Order By: Relevance
“…This is further reinforced through the increased predictive power of some risk factors in the 2014 sample; for example, while fewer participants report having friends who drink alcohol, this risk factor had a stronger association with alcohol use in 2014 compared to 2011. Similarly, the findings are consistent with previous studies regarding the influence of perceived social norms on adolescent behaviour; as adolescent drinking declines, the socially normative nature of this behaviour also declines [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…This is further reinforced through the increased predictive power of some risk factors in the 2014 sample; for example, while fewer participants report having friends who drink alcohol, this risk factor had a stronger association with alcohol use in 2014 compared to 2011. Similarly, the findings are consistent with previous studies regarding the influence of perceived social norms on adolescent behaviour; as adolescent drinking declines, the socially normative nature of this behaviour also declines [33][34][35].…”
Section: Discussionsupporting
confidence: 91%
“…It is important to state that the role of normative beliefs in prevention programs still remains controversial [5961]. Two studies from the same group [62,63] found contradictory results among college students and their perceptions and attitudes towards alcohol [59]. Posterior analyses of the same samples found that interventions focusing on normative beliefs had variable efficacy, according to the characteristics of the communities where they were implemented [64].…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides strong evidence for the impact of social norms on a variety of behaviors, including alcohol consumption (Padon, Rimal, Jernigan, Siegel, & DeJong, 2016; Pedersen et al, 2017; Rimal, 2008; Rimal & Mollen, 2013), tobacco use (Ali & Dwyer, 2009; Mead, Rimal, Ferrence, & Cohen, 2014; Mereish, Goldbach, Burgess, & DiBello, 2017), cannabis use (Ecker & Buckner, 2014; Mereish et al, 2017), healthy food consumption (Mollen, Rimal, Ruiter, & Kok, 2013), contraceptive use (Rimal & Lapinski, 2015), and HIV testing (Batona, Gagnon, Simonyan, Guedou, & Alary, 2015). Findings on the role of norms do vary, however.…”
mentioning
confidence: 99%